Agency for Learning: Intention, Motivation, Self-Efficacy and Self-Regulation - Code, Jillianne (Frontiers in Education, 2020)
Agency is inherent in students’ ability to regulate, control, and monitor their own learning. A learners' effectiveness in regulating their cognitive, affective, and behavioural processes as they interact within the learning environmental is critical to their academic success. This article advances a theory of learner agency, or agency for learning, as an emergent capacity that is intentional, self-generated, and reactive to social factors in the learning context. This article further traces the development of the Agency for Learning Questionnaire (AFLQ) and examines the internal consistency, predictive validity, and psychometric properties covering four dimensions of agentic functioning including intentionality (planfulness, decision competence), forethought (intrinsic and extrinsic motivation), self-regulation, and self-efficacy. Results of this research demonstrate that the AFLQ provides a reliable, valid, multidimensional measure of agency for learning based on existing theoretical and empirical findings, advancing both theory and practice. Understanding how agency develops and emerges within learning environments is a key factor in identifying why learning occurs enabling educational psychologists to potentially identify, measure, and study agentic processes in the context of learning across a variety of research designs.